Ge nanoislands grown by radio frequency magnetron sputtering: comprehensive investigation of surface morphology and optical properties - Samavati, Alireza (Hindawi Publishing, 2015)
The comprehensive investigation of the effect of growth parameters on structural and optical properties of Si-based single layer Ge nanoislands grown via Stranski-Krastanov mechanism employing radio frequency magnetron sputtering due to its high deposition rate, easy procedure, economical cost, and safety is carried out. The estimated width and height of Ge nanoislands produced by this technique are in the range of ~8 to ~30 and ~2 to 8 nm, respectively. Varieties parameters are manipulated to optimize the surface morphology and structural and optical behavior of Ge nanoislands. The resulted nanoislands are analyzed using various analytical techniques including atomic force microscope, X-ray diffraction, energy dispersive X-ray spectroscopy, room temperature photoluminescence, and Raman spectroscopy. The optimum parameters for growing high quality samples having high number density and homogenous and small size distribution are found to be 400°C for substrate temperature, 300 sec for deposition time, 10 sccm for Ar flow, and 100 W for radio frequency power. The excellent features of the results suggest that our systematic investigation on the organized growth factors and their effects on surface parameters and photoluminescence emission energy may constitute a basis for the tunable growth of Ge nanoislands (100) nanoislands suitable in nanophotonics